Problem regions and State policy in the field of regional economy - A. Z. Sapiev; N. N. Galinskaya (Новые технологии, 2022)
Now, there are no generally accepted ideas about the types of regions, there is no modern classification of regions according to the regional economic policy being implemented. This is the most important task in the regional policy of the state at the moment. There is a need to identify depressive regions with the help of such classification, to determine the economic levers with which it is possible to solve the most acute and important problems of such regions, as well as to determine the ways of development of these regions. As a result of such an analysis of the situation, federal aid should go to those regions that are most in crisis and that really need it. Various methodological approaches to the classification of regions for solving such problems are considered. Due to the complexity of analyzing the effectiveness of regional policy for individual regions, modern tools cannot provide an accurate answer to the question about the state of the region’s economy. There are no clear criteria for whether a given region is located in backward or depressed areas. All this affects the state of things and develops due to the inability to objectively assess and compare all the conditions for the development of the region and take into account all the data in a complex. As a result of the above and taking into account the limited resources of the federal center, territorial classification in the field of federal assistance is required. In many countries, there is a widespread practice combining quantitative and expert assessments when making decisions in the field of federal assistance to the region. The proposed typologization will make it possible to provide federal assistance to those regions that are most in crisis and that really need it.